Substantiation of the Regulatory Function of the Use of Local Food Products and Medicinal Plants for Toxic Liver Damage in Experimental Animals - Nishanov, Yusubjon Nishanovich; Askarovna, Hamrakulova Mukaddaskhon; Usmanovich, Sadikov Askar; Batirovich, Navruzov Ernazar; Turginbaevich, Mamasaidov Jamolidin (International Journal of Psychosocial Rehabilitation, 2020)
recent years, the development of horticulture and the production of fruits and vegetables in the Republic of Uzbekistan has focused on the application of innovative technologies in the field of plant protection. Which is achieved through the use of modern technologies used by our gardeners and farmers not only for the production of competitive quality products, but also against pests using chemicals and pesticides. In this regard, the prevention of complications that develops with toxic damage to various diseases of the internal organs, by studying the morphological and functional changes that arise as a result of the effects of these pesticides on the body, especially the respiratory and nervous systems, is of great practical importance for improving and applying pathogenetically substantiated preventive measures. The aim of this work was to evaluate the functional state of the liver by morphological and clinical biochemical studies to assess the degree of structurally functional changes in animals poisoned by Bagira pesticide, as well as by assessing the degree of influence of food and dishes prepared from local food products, additional introduction of the complex into the diet local herbal medicines to the body as a wholeThe experiments were carried out on 147 white male rats weighing 170-190 g. Bagira pesticide at a dose of 1/20 LD50 - 44.3 mg / kg (LD50 = 886 mg / kg) was administered daily intragastrically. results of our studies, which show that the use of food prepared from local products together with decoction of medicinal plants in the experiment, showed a sharp improvement in biochemical parameters and functional state of the liver in rats with chronic liver damage with Bagira pesticide, compared with animals that are on the diet of vivarium. Reliable indicators were obtained on increasing the functional capabilities of the liver and the positive effect of new diets on the excretory function of the liver and biliary tract in experimental animals. 1. The use in the experiment of feed prepared from local products together with a decoction of medicinal plants affects the biochemical parametersand the functional state of the liver positively, compared with the indicators of animals on the diet of vivarium. 2. An increase in the amount of protein in the liver tissue, a decrease in the activity of ALT and AST of this category of animals indicates an increase in the functional capabilities of the liver, and a decrease in the content of bilirubins indicates their positive effect on the excretory function of the liver.